2017
DOI: 10.4102/ajod.v6i0.359
|View full text |Cite
|
Sign up to set email alerts
|

Forgotten, excluded or included? Students with disabilities: A case study at the University of Mauritius

Abstract: BackgroundStudents with disabilities in the tertiary education sector are more than a just a phenomenon, they are a reality. In general, little attention is devoted to their needs despite the fact that they need more care and attention.ObjectivesThis paper, through a case study at the University of Mauritius, sought to answer some pertinent questions regarding students with disabilities. Does the University of Mauritius have sufficient facilities to support these students? Are students aware of existing facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Proactive advising efforts can also occur virtually. And university degree programs that are completely remote can promote increased inclusivity, with accommodations for distance learning (Pudaruth et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Proactive advising efforts can also occur virtually. And university degree programs that are completely remote can promote increased inclusivity, with accommodations for distance learning (Pudaruth et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite seemingly progressive policy, for example, the National Education Policy Act 27 of 1996, the Draft Policy for the provision of quality education and support for children with severe to profound intellectual disabilities (2016) and the Strategic Policy Framework on Disability for the Post-School Education and Training System (2018), much still needs to be done to implement and sustain initiatives that support and include students with disabilities. It is well recognised that many universities are not fully equipped to cater for disabilities (Morley & Croft, 2011;Pudaruth, Gunputh & Singh, 2017;Southern Africa Federation of the Disabled, 2018). As Morley and Croft (2011, p. 393) noted, "while awareness about exclusion and equalities is developing, disability is a structure of inequality that has received little policy or research attention in higher education in low-income countries".…”
Section: Disability In South African Higher Educationmentioning
confidence: 99%
“…Matonya (2016) taking 22 women with disabilities in one HE in Tanzania found that the students ask supports from their lecturers by following the teachers after class, for example they receive assignment and exam instructions. Pudaruth, Gunputh and Singh (2017) taking 6 SWDs in one HE of Mauritius found out that all the students revealed that they did not knew their advisors to get counseling over their requirements and challenges their challenges. Butucha (2016) in his extensive review of literature over the trend of student engagement in African HEIs comparing decades back with the 21 st century without discussing on the research trend on student engagement in HEIs in Africa.…”
Section: International Studies On Student Engagement In African Heismentioning
confidence: 99%